Formação profissional e mundo do trabalho : percepções de empresários do setor têxtil e egressos do curso técnico em vestuário-IFRS-Campus Erechim - Dias, Camila Carmona (2012)
In 2008, Law 11.892 creates under the scope of the Ministry of Education, the Federal Institutes of Education, Science, and Technology, which are institutions of superior, basic, and professional education, pluri-curricular and multi-campus. Among these institutions, there is the Federal Institute of Education, Science, and Technology of Rio Grande do Sul, which offers the Technical Course of Clothing at the Erechim Campus. In its theory, this model of institution does not include professional and technological education as to simply equip people for the market; it proposes a contextual and potential formation of human action as to break the barriers between technical and scientific teaching, articulating work, science, and culture. Aware that professional education has promoted several debates in the contemporary world, especially concerning the productive sector, which has been demanding from the worker a process of ongoing qualification and adaptation, this study aims answering to the following question: how do graduates of the Technical Course of Clothing, and executives of the clothing industry perceive professional formation and the relationship with the workplace? Thus, it is aimed to analyze the perception of graduates and executives on the relationship between professional formation of the Technical Course of Clothing of IFRS Erechim campus and the workplace. It is a qualitative study with data collection performed through a semi-structured interview. The participating subjects were graduates from the Technical Course of Clothing from the classes of 2009 and 2010, and executives of the clothing industry in Erechim. Based on the results of the research, it was identified that the Technical Course of Clothing has some deficiencies that impair the preparation of students for the workplace. The analysis and discussions originated from the results of this study may be relevant to the formation of future graduates, and it may also serve as subsidy to the teaching staff and coordination for creating new strategies that prioritize the quality of teaching and learning promoted by the Course.